Identifying and ranking the human resources management criteria influencing on organizational performance using MADM Fuzzy techniques - Saeed Safari; Mohammad Vazin Karimian; Ali Khosravi (Management Science Letters)
Human resources management plays essential role for the success of organizations. This paper presents an empirical investigation to determine human resource management main criteria and sub-criteria based on a survey on the existing literatures and theoretical principles. The study has been applied in a municipality organization in Iran. The study uses analytical hierarchy process as well as fuzzy technique for order preference by similarity to ideal solution (TOPSIS) for prioritizing decision tree criteria. The results indicate job design and human resource planning criteria are ranked as the highest ones. In addition, employee recruitment and selection, employee health and hygiene, training and development and compensation system criteria are other important criteria.